AB0413 Induction and progression of subcutaneous nodulosis in rheumatoid arthritis patients treated with tocilizumab. (15th June 2017) - Talotta, R; Batticciotto, A; Ditto, MC; Gerardi, MC; Ventura, D; Puttini, P Sarzi
Abstract : Background: Tocilizumab (TCZ) is a monoclonal antibody (moAb) directed against the IL-6 receptor approved for moderate-to severe rheumatoid arthritis (RA) treatment. Some authors have reported a beneficial effect of TCZ in preventing lung and subcutaneous nodulosis in RA patients. On the contrary, to our knowledge no data concerning the acceleration of subcutaneous nodulosis under TCZ therapy are currently available. Objectives: We report a small case series of 5 RA patients experimenting an evident worsening of subcutaneous nodulosis during the treatment with intravenous tocilizumab. Methods: Our cohort included 5 patients (1 male and 4 females, mean age ± Standard Deviation (SD) 64±10.6 years, mean disease duration ± SD 21.8±10.9 years). Four patients were rheumatoid factor and anti-citrullinated peptide antibodies positive. Each patient had been previously treated with several conventional and biologic drugs. At the time of observation, three subjects were practicing methotrexate (MTX), two patients were taking hydroxychloroquine (HCQ) and one patient was taking prednisone. Intravenous tocilizumab 8 mg/kg every 4 weeks was administered for a mean ± SD of 43.4±32.4 months, with a good disease control in 3 cases. All the patients had a previous history of subcutaneous nodulosis that considerably worsened during the treatment with tocilizumab. Patients experimented the development of new subcutaneous nodules localized at the fingers, elbows or the inframammary fold, tending to ulceration. The management of this medical event included the tapering of MTX, the administration of steroids, the addition of HCQ, the use of antibiotics and surgery. However, neither pharmacological nor surgical treatment was completely effective, as nodules tended to recur and to increase in number and dimensions. Results: To our knowledge this is the first report describing an accelerated subcutaneous nodulosis in a small cohort of RA patients treated with tocilizumab. Disclosure of Interest: None declared